Enhancing retail operations: Dynamic fulfilment strategies in Omnichannel retail - İskender, Hümeysa and Dayanıklı, Sinem and Kökçam, Abdullah Hulusi and Stević, Željko and Turgay, Safiye and Baydaş, Mahmut and Bunevska Talevska, Jasmina (Serbian Journal of Management, 2024)
This study explores the trend of in-store fulfillment in omnichannel retail, where nearby store inventories are utilized for online order fulfillment. This model presents advantages such as faster delivery, cost reduction, improved stock management, increased sales, and enhanced customer satisfaction. Operational challenges include determining the optimal fulfillment location for online orders. Investigating a retailer with online and brick-and-mortar stores, this paper addresses dynamic order fulfillment decisions considering customer demand and shipping cost uncertainties. The study employs Stochastic Dynamic Programming for shorter periods and the Genetic Algorithm for longer periods, revealing that the Genetic Algorithm provides solutions closely approximating optimal.